Individualism and Collectivism at Work in an Era of Deindustrialization: Work Narratives of Food Delivery Couriers in the Platform Economy - Stewart, Paul; Shanahan, Genevieve; Smith, Mark (Frontiers in Sociology, 2020)
Supposedly emblematic of digital capitalism, the rise of the gig economy is frequently taken as a cipher for the developing deindustrialisation of western societies. It is tempting to interpret the shift of manufacturing jobs to the global south and their replacement with service sector jobs as a one-way street, leading to the demise of decent work and the rise of work characterized by precarity, low pay, low skill and a non-unionized workforce. However, the reality is inevitably more complex. In the first place, pessimism may be attributed to a rose-tinted view of the experience of former industrial employment in the global north resulting from a questionable assumption about the nature of the jobs that occupied most people in former industrial societies. Certainly, deindustrialisation is not leading to “de-working,” that is, working less for the same money. With respect to gig work, autonomy and flexibility are central to labor inducement and hence labor control. Yet at the same time, and linked to the latter, we need to explore another deep-rooted phenomenon: the persistence of workspace collectivism. Our evidence derives from qualitative interviews with gig workers in the food delivery sector in a number of European countries. We highlight the extent to which couriers profess a variety of understandings of the character of platform economy labor processes. A range of narratives emerge including platform work as leisure, as economic opportunity, and as collectivist labor. Moreover, individuation, attendant upon the character of the physical labor process, did not lead in any straightforward way to individualism in social labor processes—contrary to our expectations, we in fact witnessed forms of collectivism. Collectivism is to be distinguished from “types of solidarity” described by Morgan and Pulignano (2020) whereby neo-liberalism has transformed a range of institutional forms of labor solidarities. By contrast, we are concerned with the persistence of the collective worker within the changing sociological structure of work. This echoes the earlier finding by Stephenson and Stewart (2001) that collectivism endures even when behaviourally absent and indeed even in the context of individualized working—termed “whispering shadow.” Thus, the objective of the paper is to explore the forms of actor individualism and collectivism identified in our research. Given platform apps' external control, the gig economy spatially separates workers while at the same time requiring cognition of colleagues' collective work and labor process. Notwithstanding structural processes separating workers-in-work, platforms also witness the instantiation of forms of collectivism. Deindustrialisation is neither the end to collectivism nor trade unionism. Rather than post-work, then, we explore the problematics of plus work and variant collectivisms.